2019
DOI: 10.1097/mcg.0000000000001114
|View full text |Cite
|
Sign up to set email alerts
|

An Intraprocedural Endoscopic Cleansing Device for Achieving Adequate Colon Preparation in Poorly Prepped Patients

Abstract: Background and Aims: An effective bowel preparation is essential for quality colonoscopy. Inadequate preparation results in missed lesions, need for earlier repeat procedures, prolonged colonoscopy duration, an increased likelihood of adverse events, reduced patient satisfaction, and increased costs. The MOTUS GI Pure-Vu System (Tirat Carmel, Israel) is an Food and Drug Administration-cleared device designed to improve visualization in an inadequately prepared colon by facilitating intraprocedural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…A feasibility study including 47 outpatients at 3 clinical sites who were prescribed a minimal preparation of 20 mg Bisacodyl reported high rates of cecal intubation (97.9%), significant improvement in Boston Bowel Preparation Score (BBPS) scores (from a median score of 3.0 pre Pure-Vu to 9.0 post Pure-Vu cleansing), and high rates of physician satisfaction regarding system usability [ 8 ]. An additional study of 50 outpatients who were prescribed a minimal preparation of 20 mg Bisacodyl showed that Pure-Vu significantly increased BBPS scores and increased the proportion of patients with an adequate cleansing level (31% of patients at baseline to 98% post Pure-Vu cleansing; p < 0.001) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A feasibility study including 47 outpatients at 3 clinical sites who were prescribed a minimal preparation of 20 mg Bisacodyl reported high rates of cecal intubation (97.9%), significant improvement in Boston Bowel Preparation Score (BBPS) scores (from a median score of 3.0 pre Pure-Vu to 9.0 post Pure-Vu cleansing), and high rates of physician satisfaction regarding system usability [ 8 ]. An additional study of 50 outpatients who were prescribed a minimal preparation of 20 mg Bisacodyl showed that Pure-Vu significantly increased BBPS scores and increased the proportion of patients with an adequate cleansing level (31% of patients at baseline to 98% post Pure-Vu cleansing; p < 0.001) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The System generates a mixture of water and air that creates a high intensity pulsed vortex that is delivered through four irrigation jets to break up fecal content. The fecal matter and fluids are simultaneously removed through two suction ports in the Oversleeve and delivered into external waste receptacles [7][8][9]. The Pure-Vu Workstation which is a control and pump system also has the ability to sense the buildup of material in the suction ports and automatically purge the ports to avoid clogging thus allowing significant debris to be removed from the colon.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with early stage CRC, 23 It was further assumed that PureVu was used only in the 25% of patients who presented with inadequately prepped colons [24] in each of the above groups at an additional cost to the procedure in using PureVu of $750 [25]. Based on a systematic review of the literature which demonstrated a 2-2.1% inadequate bowel prep with PureVu [18,19] and; to be conservative, the assumption was made in the Markov model that in 5% of all cases in which PureVu was used, inadequate bowel prep occurred.…”
Section: Methodsmentioning
confidence: 99%
“…It delivers a pulsed irrigation of water and air that breaks up fecal matter and evacuates the content in inadequately prepped colons. Results from peer reviewed articles have demonstrated in inadequately prepped colons that PureVu was able to properly clean 95% of colons allowing for an adequate colonoscopy to be performed [18,19]. The purpose of this study is to examine PureVu examine in a Markov lifetime cost-effectiveness analysis comparing the use of PureVu to standard of care (SOC) for patients undergoing an outpatient colonoscopy in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Like a standard flush pump, the endoscopist uses a foot pedal to activate the device. Three recent studies have shown that the Pure-Vu system is successful in improving bowel preparation quality (39)(40)(41). Patients in these studies only received Bisacodyl prior to the procedure.…”
Section: Bowel Cleansing Devicesmentioning
confidence: 99%